Kepastian Hukum Penerapan Pidana Tambahan Uang Pengganti pada Perkara Suap dalam Tindak Pidana Korupsi - Fewu, Yoyok Fiter Haiti; Ismed, Muhammad; Fitriana, Achmad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The Crime of Corruption is not limited to acts that harm state finances,but also includes cases of bribery crime. In cases of bribery crime, the perpetrator must be held accountable for their actions by undergoing the criminal sanctions imposed on them. This study aims to analyze the imposition of additional penalties in the form of restitution in corruption crimes, particularly in bribery cases, and evaluate the reasons why judges tend not to impose restitution despite evidence that the defendant received benefits from the criminal act, by using the Theory Legal Certainty and the Theory of the Purpose of Punishment. The Research methods used in this research is normative juridical, focusing on an analysis of legislation, court decisions, and related legal theories to provide a comprehensive understanding of the legal issues at hand. The findings indicate that the application of restitution in bribery cases largely depends on the interpretation of individual judges, who often overlook the aspect of asset recovery from criminal activities. Most judges argue that bribery does not directly result in financial loss to the state, thus failing to meet the conditions for restitution as stipulated in Article 18 of Law No. 31 of 1999, as amended by Law No. 20 of 2001 on the Eradication of Corruption, which states that restitution can be applied to all forms of corruption. The legal uncertainty resulting from inconsistent application of restitution undermines the credibility of the criminal justice system and hampers more effective anti-corruption efforts. This research suggests the need for a reformulation of a more holistic legal approach, integrating aspects of philosophical justice, legal certainty, and utility. This is necessary to broaden the understanding of restitution as an instrument for recovering the proceeds of crime, rather than merely compensating for state losses. Additionally, it is recommended that law enforcement institutions, including the Supreme Court and other legal bodies, issue clearer guidelines on the application of restitution to ensure consistent and fair treatment in bribery cases